Priority-Based Tactical Message Design for DLP Load Reduction Interworking between Heterogeneous Tactical Data Links - Jang, Jongin; Lim, Jaesung (Journal of Korean Institute of Communications and Information Sciences, 2022)
In order to carry out modern warfare, tactical communication equipment mounted on various types of weapon systems must be interlocked and operated in real time without interruption of tactical information. In particular, since information sharing is limited due to different message formats between systems employing heterogeneous tactical data links, real-time conversion of message formats is very important, especially in data link processors (DLPs) supporting multiple hosts. Previously, research has been conducted to reduce traffic load in DLP. However when the traffic that can be handled by DLP exceeds the traffic that can be handled by the DLP or a high-priority tactical message occurs in bulk or repeatedly, tactical messages with a relatively low priority are continuously excluded. As a result, research to solve the problem of lack of real-time has not been conducted. In this study, a selective priority-based tactical message processing method that considers the importance of a unit weapon system and a message processing rate for reliable information sharing of all weapon systems operating even in a traffic surge situation, and a tactical message that is transmitted redundantly or lacks real-time A method of identifying and dropping was proposed. In order to verify the effectiveness of the proposed method, a virtual environment simulating the tactical data link operation environment of the Korean military was implemented, and the proposed method was implemented by applying the database(DB) access module and queue management module to the software to which the proposed method was applied. It was confirmed that it is an improved method that can reduce the load on the DLP to prevent failures due to rapid traffic, and at the same time secure reliability in information sharing of the operated weapon system.
Keywords: Data Link Processor; DLP; Tactical message